2011
DOI: 10.1111/j.1600-0897.2011.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Preliminary Study on Placental Apoptosis in Mice with Passive Immunization of Anti-Phosphatidylethanolamine Antibodies and Anti-Factor XII Antibodies

Abstract: Mice with passive immunization of aPE (or anti-LDC27) and aFXII (or anti-IPP30) produced a slight increase in fetal resorption, but markedly induced thrombosis and hemorrhage in the placenta associated with lower platelet counts and increased placental apoptosis. In addition, fewer mitotic cells, less trophoblast giant cell invasion, and more shrunken cells in the deciduas were seen. Our study supports the pathogenic role of aPE and aFXII in pregnancy complications and also suggests a beneficial role of LDC27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Recently, Velayuthaprabhu et al 31 reported a murine model in which infusion of aPE, anti-LDC27, anti-FXII, and anti-IPP30 induced thrombosis and hemorrhage in the placenta and increased placental apoptosis. Moreover, kininogen-independent IgG aPE did not affect thrombin-induced platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Velayuthaprabhu et al 31 reported a murine model in which infusion of aPE, anti-LDC27, anti-FXII, and anti-IPP30 induced thrombosis and hemorrhage in the placenta and increased placental apoptosis. Moreover, kininogen-independent IgG aPE did not affect thrombin-induced platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…22,31 Two peptides, LDC27 and IPP30 (Table I), were synthesized. 22,31 Two peptides, LDC27 and IPP30 (Table I), were synthesized.…”
Section: Rabbit Polyclonal Antibodies Immunized With Ldc27 and Ipp30mentioning
confidence: 99%
“…11,15 A subsequent study in other pregnancy complications such as intra uterine growth restriction (IUGR), preeclampsia and fetal growth restriction (FGR) reported that a great incidence of apoptosis play a leading role in such complications.…”
Section: Supporting Evidence and Evaluation Of Tf-mediated Placental mentioning
confidence: 99%
“…Therefore, recent studies elucidated the impact of placental apoptosis in the aspect of placentation and pregnancy complications in autoimmune diseases like APS. 15 Based on the crucial role of TF and inflammation in aPL-induced pregnancy loss, it would be interesting to understand the mechanism of TF in contributing inflammation either by increased index of apoptosis in placenta for aPL-induced pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%
“…A murine model in which infusion of aPEs induced thrombosis and haemorrhage in the placenta supports the role of aPEs in obstetric complications of APS. 7 The relationship between aPEs and thrombosis has also been reported. [3][4][5] aPEs have been shown in 30% of patients with a history of stroke.…”
Section: Introductionmentioning
confidence: 99%